Parental epigenetic age acceleration and risk of adverse birth outcomes: the Norwegian mother, father and child cohort study - Maria C. Magnus; Yunsung Lee; Ellen Ø. Carlsen; Lise A. Arge; Astanand Jugessur; Liv G. Kvalvik; Nils-Halvdan Morken; Cecilia H. Ramlau-Hansen; Mikko Myrskylä; Per Magnus; Siri E. Håberg (BMC Medicine)
Abstract Background Few studies have examined associations between maternal epigenetic age acceleration and adverse birth outcomes, and none have investigated paternal epigenetic age acceleration. Our objective was to assess the associations of parental (both maternal and paternal) epigenetic age acceleration in relation to birth outcomes. Methods Parental epigenetic age was estimated using seven established epigenetic clocks in 2198 mothers and 2193 fathers from the Norwegian Mother, Father, and Child Cohort Study (MoBa). Individual epigenetic age acceleration was then calculated as residuals from linear regressions of estimates from the epigenetic clocks on chronological age. Further, linear regression was used to analyze differences in continuous outcomes (gestational length and standardized birthweight), while logistic regression was used for binary outcomes (preterm birth, post-term birth, small-for-gestational age [SGA], large-for-gestational age [LGA], and pre-eclampsia), adjusting for chronological age, parity, educational level, smoking, and BMI. Results Increasing maternal, but not paternal, epigenetic age acceleration was associated with decreased gestational length for five out of six clocks, with adjusted estimates ranging from a mean 0.51-day decrease (95% CI − 1.00, − 0.02; p-value 0.043) for the Horvath clock to a 0.80-day decrease (95% CI − 1.29, − 0.31; p-value 0.002) for the Levine clock. An association with increasing maternal epigenetic age acceleration according to the DunedinPACE clock was also seen with greater standardized birthweight [mean difference 0.08 (95% CI 0.04, 0.12; p-value < 0.001]. These results were also reflected in an increased risk of spontaneous preterm birth and LGA. No associations were observed with post-term birth, SGA, or pre-eclampsia. Conclusions Maternal, but not paternal, epigenetic age acceleration is associated with shorter pregnancies and an increased risk of spontaneous preterm birth. This may suggest that women’s biological age acceleration, including factors such as metabolic and physiologic state, is an additional risk factor for preterm delivery, beyond chronological age.